2023
DOI: 10.1530/raf-22-0107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone cotreatment in sub-fertile women ≥ 40 years: a meta-analysis

Abstract: Treatment of sub-fertile women aged ≥ 40 years old (AMA) is challenging. Co-treatment with growth hormone (GH) is suggested to improve reproductive outcomes in poor responders. However, few studies, and with conflicting results, focused on women with AMA. A systematic review and meta-analysis of randomized controlled trials (RCTs) and comparative retrospective trials (CRTs) of GH cotreatment in AMA women undergoing in vitro fertilization or intracytoplasmic injection treatment using their autologous oocytes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…One study showed that pregnancy and live birth rates were significantly improved with GH cotreatment (OR = 4.12, 95% CI: 1.82–9.32]. However, subgroup analysis of this study revealed that the benefits were not seen in poor‐responder patients 30 . In a meta‐analysis of 25 trials out of which 17 were RCTs with poor responders ( n = 1723), it was seen that GH administration significantly increased EMT (mean difference = 0.38 mm).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…One study showed that pregnancy and live birth rates were significantly improved with GH cotreatment (OR = 4.12, 95% CI: 1.82–9.32]. However, subgroup analysis of this study revealed that the benefits were not seen in poor‐responder patients 30 . In a meta‐analysis of 25 trials out of which 17 were RCTs with poor responders ( n = 1723), it was seen that GH administration significantly increased EMT (mean difference = 0.38 mm).…”
Section: Discussioncontrasting
confidence: 58%
“…However, subgroup analysis of this study revealed that the benefits were not seen in poor-responder patients. 30 In a meta-analysis of 25 trials out of which 17 were RCTs with poor responders (n = 1723), it was seen that GH administration significantly increased EMT (mean difference = 0.38 mm). This was possibly the contributory factor to improved live birth rate (OR = 1.67, 95% CI: 1.13-2.49) and clinical pregnancy rate (CPR) (OR = 1.97, 95% CI: 1.43-2.72) with GH cotreatment, rather than its effects on oocytes and embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Since Homburg et al. firstly explored the effect of GH supplementation on augmenting the ovarian response to gonadotropin during controlled ovarian hyperstimulation (COH) in women relatively resistant to human menopausal gonadotropin (hMG) therapy since the 1980s ( 9 11 ), more and more studies have been implemented with different administration protocols under various clinical background, such as advanced maternal age ( 12 , 13 ), poor ovarian response ( 14 19 ), polycystic ovarian syndrome ( 20 ) or repeated implantation failure ( 21 , 22 ) et al.…”
Section: Introductionmentioning
confidence: 99%